RELIGIOUS COPING PADA INDIVIDU YANG MELAKUKAN KONVERSI AGAMA - Respianto Respianto; Yohanes Kartika Herdiyanto (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
n Indonesia, we often encountered cases of religious conversion or also called conversion. Religious conversion by Jalaluddin (2012) in general can be interpreted to change religion or converted. Individuals will experience a variety of responses regarding of their choice either of the society from the previous religion and religious communities in the new religion. Various respones occurring in individuals who perform religious conversion will make the individual demonstrate a wide range of coping strategies. Coping strategy is to be studied by researchers for individuals who perform conversions with a variety of responses that emerged from various environments around the individual. This is what researcher will find out about coping strategy in this research. This study uses qualitative research with phenomenological approach. The purpose of this study was to determine the factors that cause religion conversion, the response of family and the environment and coping strategies used by individuals who do the religion conversion. This study used four respondents and will be divided into two, namely the conversion of religion because of the wedding and do the conversion because of their own desires. The results of this study are, causes of conversions divided into two due to internal and external factors. Coping strategies were used that religious coping with three types of coping, self-directing coping style, deffering coping style, and collaborative coping style. The results of this study are, causes of conversions divided into two due to internal and external factors. Religious coping divided into 3 types which using in this case, these are, self-directing coping style, deffering coping style, and collaborative coping style, three types of coping are used at each stage of the process of religioun conversion. Religious coping give positive results to the responden into social system where the responden belong. Keywords: Religion, religion conversion, coping strategy, religious coping.